Моделирование и анализ архитектуры предприятия на основе матричного подхода - Pereverzev P. P. (Образование и наука в современных условиях, 2015)
The subject of the article is to develop a model of the relationships between business processes, organizational structure and enterprise information system. Insufficient development model of the relationship because of their great complexity and multidimensionality, caused low efficiency of interaction between business processes, organizational structure and enterprise information system. The result of a matrix model of the complex relationship between business processes, organizational structu
Keywords: организационная структура; информационная система; матрица; взаимосвязь; бизнес-процесс; interconnection; business process; organizational structure; information system; the matrix